FORMATION OF STUDENTS' CIVIL POSITION AS AN INTEGRAL PART OF THE EDUCATIONAL ACTIVITIES - Larisa N. Solovieva; Aleksey V. Chumakov (Moscow Polytechnic University, 2016)
During studentship a strong personality socialization takes place, the person determines his (her) values, cultivates civil position. At this period young people are making plans for the future, therefore the educational work at higher education institution has a special role. The article highlights the features of citizenship and patriotism education in law school on the example of the activities of the student self8government structures of Novosibirsk Law Institute (branch) of Tomsk State University.